Spherical silver powder, method for producing spherical silver powder, spherical silver powder production device, and conductive paste

JP7628981B2Active Publication Date: 2025-02-12DOWA ELECTRONICS MATERIALS CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2022075428
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-04-28
Publication Date
2025-02-12
Estimated Expiration
2042-04-28

AI Technical Summary

Benefits of technology

【0016】 本発明によれば、導電性ペースト等に用いた場合に、優れた印刷性及び低温焼結性をもたらすことが可能な球状銀粉が、その製造方法及び製造装置とともに提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628981000006
    Figure 0007628981000006
  • Figure 0007628981000007
    Figure 0007628981000007
  • Figure 0007628981000008
    Figure 0007628981000008
Patent Text Reader

Abstract

To provide a spherical silver powder which achieves excellent printability and low-temperature sinterability when used in a conductive paste and the like.SOLUTION: The present invention provides a spherical silver powder wherein the ratio of the volume-based 50% cumulative diameter D50, as determined by laser diffraction, to the BET diameter DBET is 0.9 to 1.2 inclusive and wherein the spherical silver powder contains internal voids.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a spherical silver powder, a method for producing spherical silver powder, an apparatus for producing spherical silver powder, and a conductive paste. [Background technology]

[0002] Conductive pastes used for various electronic components, including internal electrodes of multilayer capacitors, conductor patterns of circuit boards, and solar cells, are manufactured by adding silver powder together with glass frit to an organic vehicle and kneading them. The silver powder for conductive pastes is required to have a suitably small particle size, uniform particle size, and high dispersibility in order to meet the needs of miniaturization of electronic components, high density of conductor patterns, and fine lines.

[0003] As a method for producing silver powder for such conductive pastes, Patent Document 1 proposes a method for producing fine silver powder, which comprises mixing and reacting an aqueous silver nitrate solution with aqueous ammonia to obtain an aqueous silver ammine complex solution, flowing this aqueous solution through a fixed flow path (a first flow path), providing a second flow path that joins the first flow path midway, flowing an organic reducing agent through this second flow path, and contacting and mixing the two at the junction of the first flow path and the second flow path.

[0004] Patent Document 2 also proposes a method for producing silver powder in which a silver solution containing a silver complex and a reducing agent solution are each quantitatively and continuously supplied into a flow path, and the silver solution and the reducing agent solution are mixed within the flow path to obtain silver powder by quantitatively and continuously reducing the silver complex in a reaction liquid, characterized in that the ratio of the flow rate of the silver solution in a pipe forming the flow path to the flow rate of the reducing agent solution supplied in the same direction as the supply direction of the silver solution from a pipe arranged coaxially within the pipe is 1.5 or more when the silver solution and the reducing agent solution are mixed.

[0005] Furthermore, Patent Document 3 proposes a method for producing spherical silver powder in which an aqueous silver nitrate solution is mixed and reacted with aqueous ammonia to obtain an aqueous silver ammine complex solution, and the aqueous silver ammine complex solution is mixed with an aqueous reducing agent solution in the presence of seed particles and an imine compound to reduce and precipitate silver particles, in which the aqueous silver ammine complex solution and the aqueous reducing agent solution are flowed through separate flow paths that join at a confluence, and the aqueous silver ammine complex solution and the aqueous reducing agent solution are contacted and mixed at the confluence.

[0006] Furthermore, Patent Document 4 presents a method for producing silver microparticles in which ammonia and a reducing agent are added to a silver ion solution to reduce and precipitate silver microparticles, and the reducing agent is added within 20 seconds after the addition of ammonia to precipitate fine silver microparticles. However, it is said that the ammonia-added silver ion solution and the reducing solution are mixed outside the pipeline, and the only specific example disclosed is one in which a hydroquinone solution is used as the reducing agent. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2005-48236 A [Patent Document 2] JP 2015-45064 A [Patent Document 3] JP 2010-70793 A [Patent Document 4] JP 2008-255378 A Summary of the Invention [Problem to be solved by the invention]

[0008] When forming internal electrodes, conductor patterns, etc. using a conductive paste containing silver powder, the silver powder is required to have good printability when made into a conductive paste, and also to be sinterable at low temperatures (690 to 740°C) and have excellent low-temperature sintering properties in order to suppress deterioration of surrounding components due to heating during firing of the conductive paste. The silver powders obtained by the manufacturing methods described in Patent Documents 1 to 4 have room for improvement in these respects.

[0009] An object of the present invention is to provide a spherical silver powder capable of producing a conductive paste having excellent printability and low-temperature sintering properties, together with a manufacturing method and manufacturing apparatus thereof. [Means for solving the problem]

[0010] The present inventors have conducted extensive research to solve the above problems, and have determined that in order to simultaneously obtain excellent low-temperature sintering properties and printability, it is necessary to have voids within each particle of the spherical silver powder, and to improve the dispersibility of such spherical silver powder by adjusting the BET diameter D BET The cumulative 50% diameter D based on the volume by laser diffraction method 50 Ratio of (D 50 / D BET ) is advantageous, and the present invention has been completed based on this finding. For example, the silver powder obtained by the manufacturing methods described in the above Patent Documents 1 to 4 does not have voids within each particle.

[0011] Here, the BET diameter D BET is the specific surface area (SSA) measured by the BET single point method (unit: m 2 / g) and true density (unit: g / cm 3 ) and is calculated using the formula: D BET =6 / (SSA) / true density It can be calculated as follows. D 50 , D BET The SSA and true density are values ​​measured by the method described in the Examples.

[0012] Silver powder particles are usually not completely separated, and may consist of multiple particles agglomerated together. When measuring particle size using the laser diffraction method, the particle size is calculated from the diffraction pattern of the particles, so the particle size measured is that of the particles in an agglomerated state. On the other hand, the BET single point method measures the specific surface area using the amount of gas adsorbed to the particle, and the BET diameter converted from this specific surface area indicates the particle size (particle diameter) of the particle when the measured particle is assumed to be a perfect sphere. Ratio (D 50 / D BET ) closer to 1 means there is less aggregation and the particles are closer to monodisperse.

[0013] Here, silver powder that has voids within the particles is prone to have uneven surfaces, and the ratio (D 50 / D BET ) is difficult to control to a value close to 1. The inventors flowed a silver-containing solution through a flow path, added a complexing agent at a complexing agent addition position in the flow path, added formalin at a formalin addition position downstream of the complexing agent addition position, and reduced and precipitated silver powder in the flow path. This produced a silver powder having a ratio (D 50 / D BET ) is 0.9 or more and 1.2 or less, and the present invention has been completed based on this finding.

[0014] In the manufacturing method of the present invention, a silver-containing solution is passed through a flow path, and a complexing agent is added to the flow path at a complexing agent addition position midway through the flow path to form a silver complex formation region, and formalin is added to the flow path at a formalin addition position downstream of the complexing agent addition position to form a reduction and precipitation region of silver powder. In this way, the silver complex formation region and the reduction and precipitation region are formed continuously, and further reduction and precipitation is performed using formalin as a reducing agent, thereby forming particles having voids inside while having a ratio (D 50 / D BET ) is 0.9 or more and 1.2 or less, and it is presumed that a spherical silver powder with good dispersibility can be obtained.

[0015] The gist of the present invention is as follows. [1] BET diameter D BETThe cumulative 50% diameter D based on the volume by laser diffraction method 50 The ratio of is 0.9 or more and 1.2 or less, and the particles have voids inside. [2] True density is 9.0g / cm 3 More than 10.0g / cm 3 The spherical silver powder of [1] above, which is as follows: [3] D above 50 The spherical silver powder of [1] or [2] above, wherein the particle size is 0.2 μm or more and 3.5 μm or less. [4] BET specific surface area is 0.17m 2 / g or more 3.23m 2 / g or less. [5] Any of the spherical silver powders of [1] to [4] above, in which the value obtained by subtracting the carbon, nitrogen and oxygen contents from the ignition loss is less than 0.10 mass%. [6] Any of the spherical silver powders of [1] to [5] above, in which the ratio of oxygen content to carbon content is 1.5 or more. [7] A method for producing spherical silver powder, comprising: flowing a silver-containing solution through a flow path; adding a complexing agent to the flow path at a complexing agent addition position midway through the flow path; adding formalin to the flow path at a formalin addition position downstream of the complexing agent addition position; and reducing and precipitating silver powder within the flow path. [8] The method for producing spherical silver powder according to [7] above, wherein the time required for the silver-containing solution to flow from the complexing agent addition position to the formalin addition position is 0.1 seconds or more and 10 seconds or less. [9] A method for producing spherical silver powder according to [7] or [8] above, wherein a surface treatment agent is added to the flow path between the complexing agent addition position and the formalin addition position, or downstream of the formalin addition position.

[10] The method for producing spherical silver powder according to any one of [7] to [9] above, wherein the formalin is added from multiple directions at the formalin addition position, and each of the multiple directions forms an angle of 75 degrees or more and 105 degrees or less with respect to the flow path.

[11] A silver powder manufacturing apparatus in which a complexing agent and formalin are added to a silver-containing solution to reduce and precipitate silver powder, the apparatus comprising: a pipe forming a flow path for the silver-containing solution; a complexing agent addition section connected to the pipe; and a formalin addition section connected to the pipe downstream of the complexing agent addition section.

[12] A conductive paste containing the spherical silver powder according to any one of [1] to [6] above, an organic binder and a solvent.

[13] The conductive paste according to

[12] above, for forming electrodes for solar cells. Effect of the Invention

[0016] According to the present invention, a spherical silver powder capable of providing excellent printability and low-temperature sintering property when used in a conductive paste or the like is provided, together with a manufacturing method and manufacturing apparatus thereof. [Brief description of the drawings]

[0017] [Figure 1] 1 is an external perspective view of an example of a silver powder manufacturing apparatus of the present invention. [Diagram 2] 2 is an external oblique view of another example of a silver powder manufacturing apparatus of the present invention. FIG. [Figure 3A] 1 is an SEM photograph (10,000x) of the silver powder of Example 1 (before vacuum drying). [Figure 3B] 1 is an SEM photograph (10,000x) of the silver powder of Example 1 (after vacuum drying and crushing treatment). [Figure 3C] 1 is an FE-SEM photograph (20,000x) of a cross section of the silver powder of Example 1 (after vacuum drying and crushing treatment). [Figure 4A] 1 is an SEM photograph (10,000x) of the silver powder of Example 2 (before vacuum drying). [Figure 4B] 1 is an SEM photograph (10,000x) of the silver powder of Example 2 (after vacuum drying and crushing treatment). [Figure 4C] 1 is an FE-SEM photograph (20,000x) of a cross section of the silver powder of Example 2 (after vacuum drying and crushing treatment). [Figure 5A] 1 is an SEM photograph (10,000x) of the silver powder of Example 3 (before vacuum drying). [Figure 5B] 1 is an SEM photograph (10,000x) of the silver powder of Example 3 (after vacuum drying and crushing treatment). [Figure 5C] 1 is an FE-SEM photograph (20,000x) of a cross section of the silver powder of Example 3 (after vacuum drying and crushing treatment). [Figure 6A] 1 is an SEM photograph (10,000x) of the silver powder of Example 4 (before vacuum drying). [Figure 6B] 1 is an SEM photograph (10,000x) of the silver powder of Example 4 (after vacuum drying and crushing treatment). [Figure 6C] 1 is an FE-SEM photograph (20,000x) of a cross section of the silver powder of Example 4 (after vacuum drying and crushing treatment). [Figure 7A] 1 is an SEM photograph (10,000x) of the silver powder of Example 5 (before vacuum drying). [Figure 7B] 1 is an SEM photograph (10,000x) of the silver powder of Example 5 (after vacuum drying and crushing treatment). [Figure 7C] 1 is an FE-SEM photograph (20,000x) of a cross section of the silver powder of Example 5 (after vacuum drying and crushing treatment). [Figure 8A] 1 is an SEM photograph (10,000x) of the silver powder of Example 6 (before vacuum drying). [Figure 8B] 1 is an SEM photograph (10,000x) of the silver powder of Example 6 (after vacuum drying and crushing treatment). [Figure 8C] 1 is an FE-SEM photograph (20,000x) of a cross section of the silver powder of Example 6 (after vacuum drying and crushing treatment). [Figure 9A] 1 is an SEM photograph (10,000x) of the silver powder of Example 7 (before vacuum drying). [Figure 9B] 1 is an SEM photograph (10,000x) of the silver powder of Example 7 (after vacuum drying and crushing treatment). [Figure 9C] 1 is an FE-SEM photograph (20,000x) of a cross section of the silver powder of Example 7 (after vacuum drying and crushing treatment). [Figure 10A] 1 is an SEM photograph (10,000x) of the silver powder of Comparative Example 1 (before vacuum drying). [Figure 10B]1 is an SEM photograph (10,000x) of the silver powder of Comparative Example 1 (after vacuum drying and crushing treatment). [Figure 10C] 2 is an FE-SEM photograph (20,000x) of a cross section of the silver powder of Comparative Example 1 (after vacuum drying and crushing treatment). [Figure 11A] 1 is an SEM photograph (10,000x) of the silver powder of Comparative Example 2 (before vacuum drying). [Figure 11B] 1 is an SEM photograph (10,000x) of the silver powder of Comparative Example 2 (after vacuum drying and crushing treatment). [Figure 11C] 2 is an FE-SEM photograph (20,000x) of a cross section of the silver powder of Comparative Example 2 (after vacuum drying and crushing treatment). [Figure 12] 1 is a chart showing the heat shrinkage rates of Example 1 and Comparative Examples 1 and 2. [Figure 13] FIG. 13 is a diagram showing the shape of an electrode pattern for performing an EL evaluation of fine line printability. [Figure 14] 1 is a photograph showing the EL evaluation results of a conductive paste using the silver powder of Example 1. [Figure 15] 1 is a photograph showing the EL evaluation results of a conductive paste using the silver powder of Example 2. [Figure 16] 1 is a photograph showing the EL evaluation results of a conductive paste using the silver powder of Example 3. [Figure 17] 1 is a photograph showing the EL evaluation results of a conductive paste using the silver powder of Example 4. [Figure 18] 1 is a photograph showing the EL evaluation results of a conductive paste using the silver powder of Example 5. [Figure 19] 1 is a photograph showing the EL evaluation results of a conductive paste using the silver powder of Example 6. [Figure 20] 1 is a photograph showing the EL evaluation results of a conductive paste using the silver powder of Comparative Example 1. [Figure 21] 1 is a photograph showing the EL evaluation results of a conductive paste using the silver powder of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] <Spherical silver powder> The spherical silver powder of the present invention has a BET diameter D BET The cumulative 50% diameter D based on the volume by laser diffraction method 50 Ratio of (D 50 / D BET ) is 0.9 or more and 1.2 or less, and the particles have voids inside. Here, the spherical shape includes a nearly spherical shape, and refers to a shape having an average aspect ratio (average ratio of major axis / minor axis) of 1.5 or less. The voids inside the particle are closed voids that are not connected to the outside. The fact that spherical silver powder has voids inside the particles can be confirmed by observing the cross-section of the particles using a field emission scanning electron microscope (FE-SEM) and seeing the presence of voids inside the particles.

[0019] Ratio(D 50 / D BET ) is preferably 1.20 or less, more preferably 1.15 or less, and even more preferably 1.04 or less, in terms of obtaining excellent dispersibility. This ratio is usually 0.90 or more, and more preferably 0.95 or more.

[0020] D 50 From the viewpoint of ease of handling of the paste when made into a conductive paste, the thickness is preferably 0.2 μm or more, and more preferably 0.5 μm or more. 50 is preferably 3.5 μm or less, and more preferably 3.0 μm or less, because appropriate particle activity can be obtained, it is advantageous in terms of low-temperature sintering of the wiring pattern formed using the conductive paste, and it is easy to respond to high density, etc.

[0021] The spherical silver powder of the present invention has a cumulative 10% diameter D 10 However, it is preferably 0.1 μm or more and 2.0 μm or less. The spherical silver powder of the present invention has a cumulative 90% diameter D 90 However, it is preferably 0.5 μm or more and 7.0 μm or less. D 10 and D. 90 is a value measured by the method described in the Examples.

[0022] The BET specific surface area (SSA) is set to 0.17 m, because it provides suitable particle activity, is advantageous in terms of low-temperature sintering of the wiring pattern formed using the conductive paste, and is easy to handle for high density applications. 2 / g or more is preferable, and 0.20m 2 / g or more. In addition, from the viewpoint of ease of handling of the paste when made into a conductive paste, 2 / g or less, and more preferably 2.40m 2 / g or less.

[0023] The true density of silver is 10.49 g / cm 3 However, the spherical silver powder of the present invention has voids inside the particles and has a true density of 9.0 g / cm 3 More than 10.0g / cm 3 The true density can be 9.4 g / cm or less, which is easy to deal with high density wiring patterns. 3 From the viewpoint of low-temperature sintering, 9.9 g / cm or more is preferable. 3 The following is preferred:

[0024] D BET is the specific surface area (m2) measured by the BET single point method 2 / g) and true density (g / cm 3 ) is used to calculate the BET diameter (μm) using the following formula: BET diameter=6 / specific surface area / true density D BET is preferably 0.18 μm or more, more preferably 0.45 μm or more, and is preferably 3.90 μm or less, more preferably 3.20 μm or less.

[0025] The spherical silver powder of the present invention has a tap density of 2.5 g / cm3 in order to facilitate application to high-precision patterns and the like. 3 It is preferable that the content is equal to or more than 4.5 g / cm. 3 On the other hand, when considering the true density of silver and the closest packing of uniform spherical powder, the upper limit of the tap density is 7.8 g / cm 3 It is.

[0026] The spherical silver powder of the present invention preferably has an ignition loss of 2.65% by mass or less, more preferably 1.62% by mass or less, where the ignition loss is measured under the conditions described in the Examples. Moreover, the spherical silver powder of the present invention preferably has a carbon content of 1.00 mass% or less, more preferably 0.50 mass% or less, a nitrogen content of 0.15 mass% or less, more preferably 0.12 mass% or less, and an oxygen content of 1.50 mass% or less, more preferably 1.00 mass% or less. From the viewpoint of low-temperature sintering, the oxygen content is preferably 0.20 mass% or more, more preferably 0.30 mass% or more. The carbon, nitrogen and oxygen contents are values ​​measured by the methods in the Examples. From the viewpoint of low-temperature sintering, the ratio of oxygen content to carbon content (O / C) is preferably 1.5 or more, preferably 3.5 or less, and more preferably 1.7 to 3.0. In particular, when the spherical silver powder of the present invention is used in a conductive paste containing glass frit, the oxygen contained in the silver particles helps generate heat, accelerating the softening of the glass, which is advantageous in terms of low-temperature sintering. Furthermore, the spherical silver powder of the present invention preferably has a value obtained by subtracting the total content of carbon, nitrogen and oxygen from the ignition loss of less than 0.10% by mass, more preferably 0.09% by mass or less. If the value is within this range, problems with thermal expansion can be easily avoided when parts such as electrodes are formed using the spherical silver powder of the present invention.

[0027] <Manufacturing method of spherical silver powder> The method for producing spherical silver powder of the present invention includes flowing a silver-containing solution through a flow path, adding a complexing agent at a complexing agent addition position in the flow path, adding formalin at a formalin addition position downstream of the complexing agent addition position, and reducing and precipitating silver powder in the flow path. In the production method of the present invention, the silver-containing solution, the complexing agent, and formalin are continuously supplied and quantitatively mixed, thereby maintaining constant the rate of formation of the silver complex and the rate of reduction and precipitation of the silver powder, and thus quantitatively and continuously obtaining the desired spherical silver powder.

[0028] The silver-containing solution is a solution that reacts with a complexing agent to form a silver complex, and a solution containing a silver salt can be used. Examples of the solution include aqueous solutions of silver nitrate, silver chloride, silver formate, silver oxalate, and silver sulfate, and an aqueous solution of silver nitrate is preferred from the viewpoint of availability.

[0029] From an economical viewpoint, the silver concentration of the silver-containing solution is preferably 0.01 mol / L or more, more preferably 0.05 mol / L or more. From the viewpoint of ensuring the interparticle distance of the particles after reduction precipitation and suppressing aggregation, the silver concentration is preferably 0.5 mol / L or less, more preferably 0.3 mol / L or less.

[0030] The flow velocity of the silver-containing solution is preferably 0.45 m / sec or more, more preferably 0.65 m / sec or more, from the viewpoints of productivity and monodisperse particle formation, and is preferably 3.20 m / sec or less, more preferably 2.70 m / sec or less, from the viewpoints of aggregation inhibition and monodisperse particle formation.

[0031] In the manufacturing method of the present invention, a silver-containing solution is flowed through a flow channel, and a complexing agent is added at a complexing agent addition position midway through the flow channel to form a silver complex.

[0032] Examples of the complexing agent include ammonia, ammonium salts, citric acid, acetic acid, etc., and among these, ammonia is preferred. Ammonia can be added in the form of aqueous ammonia. For example, when ammonia water is added as a complexing agent, a silver ammine complex is formed. The silver ammine complex is preferable because it can be easily reduced by formalin. The amount of ammonia water added is preferably an amount in which silver ions that do not form a silver ammine complex are substantially not left in the solution, and the amount of ammonia can be 2.6 moles or more and 11.2 moles or less, preferably 3.1 moles or more and 10.4 moles or less, per mole of silver.

[0033] From an economical viewpoint, the concentration of the aqueous ammonia is preferably 3.1 mol / L or more, more preferably 3.7 mol / L, and is preferably 16.2 mol / L or less, more preferably 15.1 mol / L or less. The flow rate of the ammonia water is preferably 0.40 m / sec or more, more preferably 0.60 m / sec or more, and is preferably 3.20 m / sec or less, more preferably 2.70 m / sec or less. When other complexing agents are used, the concentration and flow rate may be similar to those described above.

[0034] In the manufacturing method of the present invention, formalin is added to the flow path at a formalin addition position downstream of the complexing agent addition position, thereby reducing and precipitating the silver powder. By using formalin as a reducing agent, it is possible to obtain silver powder having voids inside the particles. The concentration of formalin (aqueous formaldehyde solution) is preferably 3.9 mol / L or more, more preferably 4.7 mol / L or more, and is preferably 14.5 mol / L or less, more preferably 12.8 mol / L or less.

[0035] The amount of formalin is preferably an amount that does not substantially generate unreacted silver ions, and can be an amount that provides 3.1 to 10.6 moles of formalin (formaldehyde) per mole of silver, and preferably 3.7 to 9.3 moles.

[0036] In the manufacturing method of the present invention, since formalin is added to the silver complex solution formed, the time required for the silver-containing solution to flow from the complexing agent addition position to the formalin addition position (elapsed time) is preferably 0.1 seconds or more, more preferably 0.5 seconds or more. In addition, if the complexing agent reacts with anything other than silver ions, the stability of the silver complex may increase and the reduction reaction may not proceed easily, so in order to prevent the reaction between the complexing agent and anything other than silver ions from starting, the elapsed time is preferably 10.0 seconds or less, more preferably 5.0 seconds or less. If the elapsed time is longer than 10.0 seconds, the generation of by-products during the period from the addition of the complexing agent to the addition of formalin and during the reduction reaction will change, and the value obtained by subtracting the total content of carbon, nitrogen and oxygen from the loss on ignition will increase. In addition, the ratio of the oxygen content to the carbon content contained in the silver particles will decrease.

[0037] In the manufacturing method of the present invention, a surface treatment agent can be added to the flow path between the complexing agent addition position and the formalin addition position, or downstream of the formalin addition position. Addition of the surface treatment agent is advantageous in terms of suppressing aggregation of the reduced and precipitated silver powder. The addition is preferably carried out at a point between the complexing agent addition position and the formalin addition position.

[0038] Examples of the surface treatment agent include fatty acids, fatty acid salts, surfactants, organic metals, chelating agents, protective colloids, etc. The surface treatment agent can be used in an amount of 0.03% by mass or more and 1.00% by mass or less based on the silver in the silver-containing solution. The surface treatment agent may be used in the form of an emulsion, a solution, etc.

[0039] (1)Fatty acid Examples of fatty acids include propionic acid, caprylic acid, lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, acrylic acid, oleic acid, linoleic acid, arachidonic acid, and ricinoleic acid.

[0040] (2) Fatty acid salts Examples of fatty acid salts include metal salts of the fatty acids described above in (1). Examples of metals include lithium, sodium, potassium, barium, magnesium, calcium, aluminum, iron, cobalt, manganese, lead, zinc, tin, strontium, zirconium, silver, and copper.

[0041] (3) Surfactants Examples of the surfactant include anionic surfactants such as alkylbenzene sulfonates and polyoxyethylene alkyl ether phosphates, cationic surfactants such as aliphatic quaternary ammonium salts, amphoteric surfactants such as imidazolinium betaine, and nonionic surfactants such as polyoxyethylene alkyl ethers and polyoxyethylene fatty acid esters.

[0042] (4) Organometallic Examples of the organic metal include acetylacetone tributoxyzirconium, magnesium citrate, diethyl zinc, dibutyl tin oxide, dimethyl zinc, tetra-n-butoxyzirconium, triethyl indium, triethyl gallium, trimethyl indium, trimethyl gallium, monobutyl tin oxide, tetraisocyanate silane, tetramethyl silane, tetramethoxy silane, monomethyl triisocyanate silane, silane coupling agents, titanate-based coupling agents, and aluminum-based coupling agents.

[0043] (5) Chelating agents Chelating agents include imidazole, oxazole, thiazole, selenazole, pyrazole, isoxazole, isothiazole, 1H-1,2,3-triazole, 2H-1,2,3-triazole, 1H-1,2,4-triazole, 4H-1,2,4-triazole, 1,2,3-oxadiazole, 1,2,4-oxadiazole, 1,2,5-oxadiazole, 1,3,4-oxadiazole, 1,2,3-thiadiazole, 1,2,4-thiadiazole, 1,2,5-thiadiazole, Examples of the chelating agent include diazole, 1,3,4-thiadiazole, 1H-1,2,3,4-tetrazole, 1,2,3,4-oxatriazole, 1,2,3,4-thiatriazole, 2H-1,2,3,4-tetrazole, 1,2,3,5-oxatriazole, 1,2,3,5-thiatriazole, indazole, benzimidazole, benzotriazole, and the like, as well as salts of these chelating agents, and polycarboxylic acids including dicarboxylic acids such as succinic acid, malonic acid, glutaric acid, and adipic acid.

[0044] (6) Protective colloids Examples of protective colloids include peptides, gelatin, albumin, gum arabic, prothalbic acid, risalbic acid, glue, and the like.

[0045] As the surface treatment agent, (1) a fatty acid is preferred, and among these, stearic acid is preferred, from the viewpoint of ease of modification of the silver particle surface. (1) The fatty acid is preferably in the form of an emulsion, such as a stearic acid emulsion.

[0046] In the manufacturing method of the present invention, the temperature of the liquid flowing through the flow path is preferably 5°C or higher, more preferably 15°C or higher, from the viewpoint of the reactivity of the reduction reaction, and is preferably 60°C or lower, more preferably 50°C or lower, from the operational viewpoint.

[0047] In the production method of the present invention, a mixer may be used to apply helical rotation in the axial direction of the flow channel to mix the liquids.

[0048] In the manufacturing method of the present invention, the liquid containing the reduced and precipitated silver powder (hereinafter also referred to as "silver powder-containing liquid") is discharged outside the flow path and collected to obtain spherical silver powder. The time from the addition of formalin to the discharge of the silver powder-containing liquid outside the flow path is preferably 1 second or more, more preferably 2 seconds or more, in order to anticipate the completion of the reduction reaction, and is preferably 10 seconds or less, more preferably 5 seconds or less, in order to prevent the silver powder from settling in the piping. In the manufacturing method of the present invention, formalin is added to the flow path at a formalin addition position downstream of the complexing agent addition position, so a reduction reaction occurs in the flow path to generate silver nuclei, which grow into silver particles in the flow path. If the reduction reaction occurs outside the flow path as in Patent Document 4, there is a risk of the surface becoming more uneven, so it is preferable to cause the reduction reaction and particle growth in the flow path as in the present invention. The shape of the silver powder can be controlled by controlling the flow rate after the addition of formalin. For example, making the flow rate after the addition of formalin slower than the flow rate of the silver complex solution before the addition is advantageous in reducing aggregation of the silver powder particles.

[0049] The silver powder-containing liquid discharged outside the flow path is filtered and washed with water to obtain a lumpy cake that contains silver powder and water and has almost no fluidity. The spherical silver powder of the present invention is obtained by drying this cake in a dryer such as a forced circulation air dryer, a vacuum dryer, or an airflow dryer. The drying can be accelerated by replacing the water in the cake with a lower alcohol or the like. The cake can be subjected to a dry crushing treatment, a surface smoothing treatment, etc. The surface smoothing treatment can be carried out by mechanically colliding particles with each other using a high-speed stirrer. Thereafter, a classification process may be performed to remove aggregates of silver powder larger than a predetermined particle size. Furthermore, the cake may be dried, crushed and classified using an integrated device capable of drying, crushing and classifying (such as Dry Meister or Micron Dryer manufactured by Hosokawa Micron Corp.).

[0050] <Silver powder manufacturing equipment> In the manufacturing method of the present invention, a spherical silver powder manufacturing device can be used that has a pipe forming a flow path for the silver-containing solution, a complexing agent addition section connected to the pipe, and a formalin addition section connected to the pipe downstream of the complexing agent addition section. The structures of the complexing agent addition section and the formalin addition section are not particularly limited.

[0051] The complexing agent addition section or the formalin addition section may be a Y-shaped pipeline or a T-shaped pipeline, respectively, and may have a structure in which a second tube is connected midway through a tube that forms a flow path for the silver-containing solution, so that the flow path for the silver-containing solution and the flow path of the second tube merge.

[0052] Alternatively, the complexing agent addition section and the formalin addition section may each be a coaxial twin-shaft pipe. Fig. 1 is a schematic diagram of an example of a silver powder production apparatus in which the complexing agent addition section and the formalin addition section are each a coaxial twin-shaft pipe. In FIG. 1, the silver powder manufacturing apparatus 1 has a pipe 2 for flowing a silver-containing solution, a complexing agent supply pipe 3 for supplying a complexing agent, and a formalin supply pipe 4 for supplying formalin. The pipe 2 is formed in a straight line, and the complexing agent supply pipe 3 and the formalin supply pipe 4 are each formed in an approximately L-shape. In the silver powder manufacturing apparatus 1, the complexing agent supply pipe 3 is arranged inside the pipe 2 so that one side of the L-shape of the complexing agent supply pipe 3 is coaxial with the pipe 2, and the formalin supply pipe 4 is arranged inside the pipe 2 downstream of this arrangement part so that one side of the L-shape of the formalin supply pipe 4 is coaxial with the pipe 2. The complexing agent supply pipe 3 and the formalin supply pipe 4 are respectively supplied toward the downstream side of the flow path of the pipe 2. The silver powder manufacturing apparatus 1 is provided with a surface treatment agent supply pipe 5 for supplying a surface treatment agent downstream of the part of the pipe 2 where the formalin supply pipe 4 is arranged. The surface treatment agent supply pipe 5 for supplying the surface treatment agent may be arranged upstream of the portion where the formalin supply pipe 4 is arranged, for example, between the complexing agent supply pipe 3 and the formalin supply pipe 4.

[0053] The silver powder manufacturing device may have a structure in which the pipe through which the silver-containing solution flows is a pipe provided with a slit having an opening facing radially outward along the inner circumference of the pipe, and a formalin supply pipe for supplying formalin is connected to the slit. It is preferable that there are at least two formalin supply pipes. By using a device having such a structure, it is possible to make the formalin enter the pipe from the slit approximately perpendicularly (for example, at an angle of 75 degrees or more and 105 degrees or less) from the entire outer circumference of the pipe.

[0054] FIG. 2 is a schematic diagram of an example of a silver powder manufacturing apparatus equipped with a formalin addition section that supplies formalin into a tube through a slit. In Fig. 2, the silver powder manufacturing apparatus 1 has a pipe 2 for flowing a silver-containing solution, a complexing agent supply pipe 3 for supplying a complexing agent, and a formalin adding member 10 for supplying formalin. Formalin supply pipes 14a and 14b are eccentrically connected to the formalin adding member 10. The formalin supplied from the formalin supply pipes 14a and 14b enters the pipe 2 from a slit provided in the pipe 2, and enters the pipe from the entire outer circumference. The silver powder manufacturing apparatus 1 in Fig. 2 is provided with a surface treatment agent supply pipe 5 for supplying a surface treatment agent to the pipe 2 upstream of the formalin adding member 10, but the surface treatment agent supply pipe 5 may be arranged downstream.

[0055] <Conductive paste> The spherical silver powder of the present invention can provide a conductive paste with excellent printability and low-temperature sintering properties, and is suitable as a conductive paste for use in internal electrodes of multilayer capacitors, conductor patterns of circuit boards, and electrodes and circuits of various electronic components including solar cells.

[0056] The conductive paste of the present invention can contain the spherical silver powder of the present invention, an organic binder, and a solvent.

[0057] The organic binder is not particularly limited, and examples thereof include silicone resin, epoxy resin, acrylic resin, polyester resin, polyimide resin, polyurethane resin, phenoxy resin, cellulose-based resin (ethyl cellulose, hydroxypropyl cellulose, etc.), etc. These may be used alone or in any combination of two or more kinds in any ratio.

[0058] The solvent is not particularly limited, and examples thereof include alcohol-based solvents such as terpineol, butyl carbitol, texanol, ethylene glycol, diethylene glycol, and glycerin, ester-based solvents such as butyl carbitol acetate and ethyl acetate, and hydrocarbon-based solvents such as toluene, xylene, and cyclohexane. These may be used alone or in any combination of two or more kinds in any ratio.

[0059] The content of the spherical silver powder of the present invention in the conductive paste can be 80% by mass or more, preferably 85% by mass or more, and can be 95% by mass or less, preferably 90% by mass or less. The content of the organic binder in the conductive paste can be 0.1 mass % or more, and preferably 0.2 mass % or more, and can be 0.4 mass % or less, and preferably 0.3 mass % or less. The content of the solvent in the conductive paste can be 6% by mass or more, and preferably 7% by mass or more, and can be 20% by mass or less, and preferably 15% by mass or less.

[0060] The conductive paste may contain, as optional components, glass frit, dispersant, surfactant, viscosity modifier, slip agent, etc. The conductive paste used in the manufacture of solar cell electrodes preferably contains glass frit, such as Pb-Te-Bi-based and Pb-Si-B-based glass frits.

[0061] The method for producing the conductive paste is not particularly limited, and includes a method of mixing the spherical silver powder of the present invention, an organic binder, a solvent, and optionally optional components. The mixing method is not particularly limited, and for example, a planetary stirrer, ultrasonic dispersion, a disper, a three-roll mill, a ball mill, a bead mill, a two-axis kneader, etc. can be used.

[0062] The conductive paste of the present invention can be applied to a substrate to form a coating film by, for example, screen printing, offset printing, printing such as photolithography, dipping, etc. The coating film may be formed into a predetermined pattern shape by photolithography using a resist.

[0063] The conductive film can be formed by firing the coating film. The firing may be carried out in air or in a non-oxidizing atmosphere such as nitrogen. The spherical silver powder of the present invention has excellent low-temperature sintering properties, and the firing temperature of the coating film can be from 600° C. to 800° C., and preferably from 690° C. to 760° C. The firing time can be from 20 seconds to 1 hour, and is preferably at least 40 seconds, and is also preferably 20 minutes or less, and more preferably 2 minutes or less.

[0064] The conductive paste of the present invention can be suitably used for forming internal electrodes of multilayer capacitors, conductor patterns of circuit boards, and electrodes and circuits of various electronic components including solar cells. EXAMPLES

[0065] Examples of the present invention will be described below, but the present invention is not limited to these examples.

[0066] [Silver powder evaluation] The silver powders of the examples and comparative examples were evaluated as follows.

[0067] <True density> The true density was measured by the constant volume expansion method (the "gas pycnometer method" in the Japanese Pharmacopoeia) using a dry-type automatic density meter (manufactured by Micromeritics, model name: AccuPyc II 1340). In the measurement of the true density, the voids closed inside the silver particles not connected to the outside are measured in a form that includes them in the density.

[0068] <BET specific surface area> The BET specific surface area was measured using a fully automatic specific surface area measuring device (manufactured by Mountech, model name: Macsorb HM-model 1210). After putting silver powder into the device and degassing it by flowing a He-N2 mixed gas (30% nitrogen) at 60°C for 10 minutes, the measurement was carried out by the BET single point method.

[0069] <D 10 、D 50 、D 90 > D 10 、D 50 、D 90 D, D, and D were measured by wet sample measurement using a laser diffraction method with a Microtrac particle size distribution measuring device (manufactured by Microtrac Bell Corporation, model name: MT-3300EXII). In the measurement, 0.1 g of the sample (silver powder) was added to 40 mL of isopropyl alcohol (IPA) and dispersed. For the dispersion, an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho, model name: US-150T; 19.5 kHz, chip tip diameter 18 mm) was used. The dispersion time was set to 2 minutes. The dispersed sample was subjected to the above device, and the particle size distribution was determined using the attached analysis software.

[0070] <Ignition loss of silver powder (Ig-Loss)> For the ignition loss, 2 g of the sample (silver powder) was weighed and placed in a magnetic crucible, and after heating strongly at 800°C for 30 minutes, which was a sufficient time to reach a constant weight, the sample was cooled and weighed to obtain the mass (w) after heating. The ignition loss (%) was calculated by the following formula. Ignition loss (%) = (2 - w) / 2 × 100 The unaccounted part is the value obtained by subtracting the measured values of the carbon, nitrogen, and oxygen contents measured by the following measurement method of <carbon, nitrogen, and oxygen contents> from the ignition loss.

[0071] <Carbon, nitrogen and oxygen content> The carbon, nitrogen and oxygen contents were measured as follows. The carbon content was determined by measuring the CO and CO2 generated when the sample (silver powder) was heated to 1350℃ in an oxygen stream and melted using a carbon-sulfur analyzer (Horiba, Ltd., device name: EMIA-810) by infrared absorption, and converting the measured value. The amount of sample (silver powder) used for the measurement was determined to be within the range of the calibration curve, based on a comparison of the intensity with that of a standard sample in a preliminary measurement. The nitrogen content was measured using an oxygen, nitrogen, and hydrogen simultaneous analyzer (LECO, device name: ONH836) with an impulse furnace power value of 4,000 W in a helium or argon atmosphere, and the nitrogen content in 0.20 g of sample (silver powder) was measured by the thermal conductivity method. The oxygen content was measured using an oxygen / nitrogen / hydrogen simultaneous analyzer (LECO, device name: ONH836) by infrared absorption method in a 0.05 g sample (silver powder) in a helium or argon atmosphere with an impulse furnace power value of 4,000 W.

[0072] <Tap density> The tap density (TAP) was determined using a tap density measuring device (manufactured by Shibayama Scientific Co., Ltd., device name: bulk specific gravity measuring device SS-DA-2). The tap density was measured as follows. 30 g of silver powder was weighed out and placed in a 20 mL test tube, and tapped 1000 times with a drop of 20 mm. The sample volume (cm3) after tapping was then measured. 3 The tap density (g / cm 3 ) is calculated using the following formula: Tap density (g / cm 3 ) = 30 (g) / sample volume after tapping (cm 3 )

[0073] [Preparation of silver powder] The silver powders of the examples and comparative examples were prepared as follows.

[0074] <Example 1> Silver powder was produced using the apparatus shown in Figure 1. A silver nitrate solution with a silver concentration of 0.13 mol / L was introduced into tube 2 (inner diameter 20 mm) at a flow rate of 21.5 L / min at a liquid temperature of 25.7°C, and about 1 second later, a 9.4 mass% ammonia solution was introduced into tube 3 (inner diameter 6 mm), a coaxial double tube, at a flow rate of 2.3 L / min to generate a silver ammine complex in tube 2. The amount of silver nitrate solution was such that the silver concentration in the total liquid volume after the addition of the complexing agent, formalin, and surface treatment agent was 0.1 mol / L. Approximately 2.23 seconds after the addition of the ammonia solution, formalin (17.4% by mass formaldehyde aqueous solution) was introduced from the coaxial double tube formalin supply pipe 4 (inner diameter 6 mm, outer diameter 8 mm) at a flow rate of 2.5 L / min to precipitate silver powder. The flow velocity of the silver complex solution before the formalin addition just before the formalin addition position was 1.50 m / s, and the flow velocity of the formalin was 1.50 m / s. Approximately 1 second after the addition of formalin, a surface treatment agent (0.17% by mass Cellosol aqueous solution. Cellosol 920 (manufactured by Chukyo Yushi Co., Ltd., containing 15.5% by mass stearic acid)) was introduced from the surface treatment agent supply pipe 5 at a flow rate of 2.5 L / min. The amount of stearic acid added relative to silver (target value) was 0.18% by mass. In this way, a silver powder-containing slurry was obtained. In the above, the distance from the ammonia aqueous solution addition position to the formalin addition position was 1.8 m, and the distance from the formalin addition position to the surface treatment agent addition position was 1.6 m.

[0075] A slurry containing silver powder was discharged from tube 2. The obtained slurry containing silver powder was subjected to solid-liquid separation, and the obtained solid was washed with pure water to remove impurities in the solid. The end point of this washing can be determined by the electrical conductivity of the water after washing. The silver powder was washed until the electrical conductivity was 0.5 mS / m or less, dried, and then crushed to obtain 310 g of silver powder. The time from the addition of the surface treatment agent to the release was 1 to 2 seconds. Other production conditions and evaluation results are shown in Tables 1 and 2. SEM photographs (10,000x) of the silver powder of Example 1 are shown in Figure 3A (before vacuum drying) and Figure 3B (after vacuum drying and crushing). Figure 3C shows a field emission scanning electron microscope (FE-SEM) (20,000x) of the cross section of a particle of the silver powder (after vacuum drying and crushing). Figure 3C shows that there are voids inside the particles.

[0076] <Example 2> In producing the silver powder of Example 2, the installation position of the surface treatment agent supply pipe 5 was changed so that the surface treatment agent supply pipe 5 was installed between the complexing agent supply pipe 3 and the formalin supply pipe 4, and the surface treatment agent was added before the addition of formalin. The distance from the position where the surface treatment agent was added before the addition of formalin to the position where the formalin was added was 17.5 cm. The other production conditions were as shown in Table 1, and the silver powder of Example 2 was produced in the same manner as in Example 1. The evaluation results are shown in Table 2. SEM photographs (10,000x) of the silver powder of Example 2 are shown in Figure 4A (before vacuum drying) and Figure 4B (after vacuum drying and crushing). Figure 4C shows an FE-SEM photograph (20,000x) of the cross section of a particle of the silver powder of Example 2 (after vacuum drying and crushing). Figure 4C shows that voids exist inside the particle.

[0077] <Examples 3 to 6> In the preparation of the silver powders in Examples 3 to 6, a silver powder manufacturing apparatus shown in FIG. 2 was used. A slit (slit width 0.44 mm) having an opening facing radially outward was provided along the inner circumference of the tube 2 (tube inner diameter 20.6 mm), and formalin was added into the tube from the entire circumference using an apparatus having a formalin addition member 10 (described as slit in Table 1) in which formalin supply pipes 14a and 14b were eccentrically connected to the slit. A surface treatment agent supply pipe 5 was installed between the formalin addition member 10 and the complexing agent supply pipe 3, so that the surface treatment agent was added before the addition of formalin. In the formalin addition member 10 in Example 5, a tube 2 with an inner diameter of 21.4 mm was used. In Examples 5 and 6, a mixer that imparts rotation to the flow was placed at the introduction position of the silver nitrate aqueous solution to perform liquid mixing. The distance from the ammonia aqueous solution addition position to the formalin addition position was 2.1 m, and the distance from the surface treatment agent addition position before the addition of formalin to the formalin addition position was 17.5 cm. Other preparation conditions were as shown in Table 1, and the silver powders of Examples 3 to 6 were prepared in the same manner as in Example 1. The evaluation results are shown in Table 2. SEM photographs (10,000x magnification) of the silver powders of Examples 3 to 6 are shown in Figures 5A to 8A (before vacuum drying) and Figures 5B to 8B (after vacuum drying and crushing treatment). Figures 5C to 8C show FE-SEM photographs (20,000x magnification) of the particle cross sections of the silver powders of Examples 3 to 6 (after vacuum drying and crushing treatment). Figures 5C to 8C show that voids exist inside the particles of the silver powders of Examples 3 to 6.

[0078] <Example 7> The silver powder of Example 7 was produced in the same manner as Example 1, except that the production conditions were changed as shown in Table 1. The evaluation results are shown in Table 2. SEM photographs (10,000x) of the silver powder of Example 7 are shown in FIG. 9A (before vacuum drying) and FIG. 9B (after vacuum drying and crushing treatment). Also, FIG. 9C shows an FE-SEM photograph (20,000x) of the cross section of a particle of the silver powder of Example 7 (after vacuum drying and crushing treatment). FIG. 9C shows the presence of voids inside the particle.

[0079] <Comparative Example 1> In producing the silver powder of Comparative Example 1, the silver powder production apparatus shown in Fig. 1 (but not equipped with the complexing agent supply pipe 3) was used. A silver nitrate aqueous solution and an ammonia aqueous solution were premixed in a tank (not shown) to prepare an aqueous silver ammine complex solution with a silver concentration of 0.12 mol / L and an ammonia concentration of 0.51 mol / L. Approximately 5 minutes after preparation, the aqueous silver ammine complex solution was introduced into the silver powder production apparatus of Fig. 1 (but not equipped with the complexing agent supply pipe 3) instead of the silver-containing solution at a liquid temperature of 30.4°C and a flow rate of 25.6 L / min into a pipe (inner diameter 20 mm). Approximately 4 seconds after the introduction of the silver ammine complex aqueous solution, formalin (18.5 mass% aqueous solution) was introduced from the inner tube (inner diameter 6 mm, outer diameter 8 mm) of the coaxial double tube at a flow rate of 2.5 L / min to precipitate silver powder. Next, a surface treatment agent (0.17% by mass Cellosol aqueous solution; Cellosol 920 (manufactured by Chukyo Yushi Co., Ltd., containing 15.5% by mass of stearic acid) was supplied from a supply tube (inner tube 6 mm) connected to the tube. The silver-containing slurry was discharged from the tube and treated in the same manner as in Example 1. Other preparation conditions and evaluation results are shown in Tables 1 and 2. SEM photographs (10,000x) of the silver powder of Comparative Example 1 are shown in Fig. 10A (before vacuum drying) and Fig. 10B (after vacuum drying and crushing treatment). Fig. 10C shows an FE-SEM photograph (20,000x) of the particle cross section of the silver powder of Comparative Example 1 (after vacuum drying and crushing treatment).

[0080] <Comparative Example 2> Except for adding the surface treatment agent before adding formalin, the silver powder of Comparative Example 2 was prepared in the same manner as in Comparative Example 1. The evaluation results are shown in Table 2. Fig. 11A (before vacuum drying) and Fig. 11B (after vacuum drying and crushing) show SEM photographs (10,000x) of the silver powder of Comparative Example 2. Fig. 11C shows an FE-SEM photograph (20,000x) of the cross section of a particle of the silver powder of Comparative Example 2 (after vacuum drying and crushing).

[0081] [Table 1]

[0082] [Table 2]

[0083] [Thermomechanical analysis (TMA)] Using the silver powders of the Examples and Comparative Examples, pellets having a roughly cylindrical shape (diameter 5 mm) were made using a pellet molding machine (a load of 50 kgf was applied for 1 minute), and these pellets were placed in a thermomechanical analysis (TMA) device (manufactured by Rigaku Corporation, device name: TMA8311) and heated from room temperature to 900°C at a heating rate of 10°C / min in an air atmosphere. The length of the pellet at room temperature was a, and the length of the pellet at the most contracted time was b. The thermal shrinkage rate was calculated from the reduction in the length of the pellet relative to the difference (ab) as c, using the following formula. The temperatures at which the thermal shrinkage rate became 10%, 20%, 50%, and 90% were determined, and the thermal expansion was evaluated. Heat shrinkage rate = c × 100 / (ab)

[0084] Table 3 shows the temperatures at which the thermal shrinkage rates of the silver powders of Examples 1 to 4, 6 to 7, and Comparative Examples 1 and 2 reached 10%, 20%, 50%, and 90%.

[0085] [Table 3]

[0086] 12 shows a chart of the measurement results of the thermal shrinkage of Example 1 and Comparative Examples 1 and 2. The vertical axis of the chart represents the ratio of the change in pellet length (shrinkage) to the difference between the pellet length at room temperature and the pellet length at the maximum shrinkage.

[0087] [Preparation of conductive paste] Using the silver powders of Examples 1 to 6 and Comparative Examples 1 and 2, conductive pastes were prepared as follows. The silver powders of the Examples and Comparative Examples were mixed in the composition ratios shown in Table 4 below and the materials shown in Table 4 were subjected to the following treatment to obtain conductive pastes. The mixture was mixed at 1400 rpm for 30 seconds using a propeller-less rotating and revolving type mixing and degassing device (AR310, manufactured by Thinky Corporation), and then kneaded by passing through a three-roll mill (80S, manufactured by EXAKT Corporation) with a roll gap from 100 μm to 20 μm.

[0088] [Table 4]

[0089] [Evaluation of printability (fine line printability)] The thin line evaluation (EL) was evaluated by forming a conductive pattern. The conductive pattern was formed as follows. First, a 154 mm solid pattern was formed on the back side of a silicon substrate for solar cells (100Ω / □) using a screen printer (Microtec, MT-320TV). Next, the conductive paste prepared using the silver powder of the examples and comparative examples was filtered through a 500 mesh, and then electrodes (finger electrodes) with a line width of 14 μm to 26 μm and electrodes (busbar electrodes) with a width of 1 mm were printed (applied) on the front side of the substrate in the pattern shown in FIG. 13 at a squeegee speed of 350 mm / sec. After hot air drying at 200°C for 10 minutes, a high-speed firing furnace IR furnace (NGK Insulators, high-speed firing test 4-chamber furnace) was used to fire at a peak temperature of 750°C and an in-out time of 41 seconds to obtain a conductive pattern.

[0090] After obtaining the conductive pattern, the presence or absence of breakage of the electrodes was confirmed using an EL / PL evaluation device (PVX330+POPLI-3C manufactured by ITES Co., Ltd.). In the EL / PL evaluation device, a current was passed through the busbar electrodes to perform EL (electroluminescence) evaluation. When there was a break in the electrode (finger electrode) between the busbar electrodes, the position of the break did not emit light and appeared black. Figures 14 to 21 show the EL evaluation results of the conductive pastes using the silver powders of Examples 1 to 6 and Comparative Examples 1 and 2. In the conductive paste using the silver powder of the comparative example, the thinner the line width, the more black parts that did not emit light due to breakage were observed, and it can be seen that the conductive paste using the silver powder of the example is capable of printing fine lines. Even when the peak temperature during firing was set to 690°C and 710°C, there were fewer breaks in the example, and light was obtained with a narrower line width, so that fine line printing was possible.

[0091] [Volume resistivity measurement] Conductive films were formed and the volume resistivity was measured for the conductive pastes using the silver powders of Examples 1 to 6 and Comparative Examples 1 and 2. The conductive films were formed as follows.

[0092] The sample for evaluating volume resistivity was made by screen printing the conductive paste. The printer used was a Micro-Tec Corporation MT-320, and the mask used was a Murakami Corporation mask (250 mesh, emulsion thickness 10 μm) with a zigzag design with a line width of 0.5 mm and a length of 128 mm. The squeegee speed during printing was 40 mm / s, and the printing pressure was 0.18 MPa. The printing target was a silicon substrate for solar cells processed into a 1-inch square. The printed sample was placed in a hot air dryer (ESPEC, LC-114) set at 200°C and left to dry for 5 minutes. After drying, it was fired in a high-speed firing test furnace (NGK, solar cell firing furnace) with the peak temperatures set to 690°C, 710°C, and 740°C for the 1-inch substrate, to obtain a conductive film. The volume resistivity was evaluated by measuring the linear resistance of the conductive film obtained with a digital multimeter (ADVANTEST, 7451A), measuring the average cross-sectional area of ​​the conductive film with a laser microscope (Keyence, VK-X1000), multiplying the linear resistance (Ω) by the average cross-sectional area, and dividing the result by the length of the conductive film to obtain the volume resistivity (μΩ·cm). The results are shown in Table 5.

[0093] [Table 5]

[0094] For the conductive films produced at any of the firing temperatures, the examples showed lower volume resistivities, indicating that the conductive paste using the silver powder of the examples is excellent in low-temperature sintering properties. [Industrial Applicability]

[0095] According to the present invention, a spherical silver powder capable of providing excellent printability and low-temperature sintering property when used in a conductive paste or the like is provided, together with a manufacturing method and manufacturing apparatus thereof. [Explanation of symbols]

[0096] 1 Silver powder manufacturing equipment 2 tubes 3 Complexing agent supply pipe 4 Formalin supply pipe 5 Surface treatment agent supply pipe 10 Formalin-added materials 14a Formalin supply pipe 14b Formalin supply pipe

Claims

1. BET diameter D BET The cumulative 50% diameter D based on the volume by the laser diffraction method 50 The ratio (D 50 / D BET ) is 0.9 or more and 1.2 or less, the ratio of the oxygen content to the carbon content is 1.5 or more, and the particles have voids inside.

2. True density is 9.0 g / cm 3 10.0g / cm or more 3 The spherical silver powder according to claim 1, wherein:

3. The above D 50 The spherical silver powder according to claim 1, wherein the particle size is from 0.2 μm to 3.5 μm.

4. BET specific surface area is 0.17m 2 / g or more 3.23m 2 The spherical silver powder according to claim 1, wherein the molecular weight is 1 / g or less.

5. 2. The spherical silver powder according to claim 1, wherein the ignition loss minus the carbon, nitrogen and oxygen contents is less than 0.10 mass%.

6. A method for producing spherical silver powder, comprising: flowing a silver-containing solution through a tubular flow path; adding a complexing agent to the flow path of the tube at a complexing agent addition position midway through the flow path of the tube; adding formalin to the flow path of the tube at a formalin addition position downstream of the complexing agent addition position; and reducing and precipitating silver powder within the flow path of the tube.

7. 7. The method for producing spherical silver powder according to claim 6, wherein the time required for the silver-containing solution to flow from the complexing agent addition position to the formalin addition position is 0.1 seconds or more and 10 seconds or less.

8. 7. The method for producing spherical silver powder according to claim 6, wherein a surface treatment agent is added to the flow path of the pipe between the location where the complexing agent is added and the location where the formalin is added, or downstream of the location where the formalin is added.

9. A method for producing spherical silver powder as described in claim 6, wherein the complexing agent is ammonia, and the amount of ammonia at the complexing agent addition position is 2.6 moles or more and 11.2 moles or less per mole of silver.

10. The method for producing spherical silver powder according to any one of claims 6 to 9, wherein the formalin is added from a plurality of directions at the formalin addition position, and the plurality of directions form angles of 75 degrees or more and 105 degrees or less with respect to the flow paths of the respective tubes.

11. A silver powder manufacturing apparatus that adds a complexing agent and formalin to a silver-containing solution to reduce and precipitate silver powder within a flow path of a tube, the apparatus comprising: a tube that forms a flow path for the silver-containing solution; a complexing agent addition section that is connected to the tube; and a formalin addition section that is connected to the tube downstream of the complexing agent addition section.

12. A spherical silver powder manufacturing apparatus as described in Claim 11, further comprising a surface treatment agent supply pipe for supplying a surface treatment agent between the complexing agent addition section and the formalin addition section, or downstream of the formalin addition section.

13. A conductive paste comprising the spherical silver powder according to any one of claims 1 to 5, an organic binder and a solvent.

14. The conductive paste according to claim 13, which is for forming an electrode for a solar cell.

Citation Information

Patent Citations

  • Superfine silver powder and method of producing superfine silver powder

    JP2005048236A

  • Method for producing silver particulate

    JP2008255378A

  • Spherical silver powder and method for producing the same

    JP2010070793A

  • Method for producing silver powder and production device therefor

    JP2011042839A

  • Silver powder, method for manufacturing the same, and conductive paste

    JP2012214873A